'Her shape' intervention programme for obese women with high breast adiposity - Juliana, N; Shahar, S; Sahar, MA; Ghazali, AR; Manaf, ZA; Noah, RM (Hec Press, Healthy Eating Club Pty Ltd, 2024)
Indexed by Scopus